2014
DOI: 10.3109/00016357.2014.887770
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of chlorine dioxide, zinc chloride and chlorhexidine solution on the gaseous volatile sulfur compounds

Abstract: The results suggest that sodium chlorite solution has the effect of eliminating gaseous VSCs directly. This must be because it can release chlorine dioxide gas which can react directly with gaseous VSCs. In the case of other solutions that have been proved to be effective to reduce halitosis clinically, it can be proposed that their anti-VSC effect is less likely due to the direct chemical elimination of gaseous VSCs in the mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…Zn 2+ , chlorine dioxide (ClO 2 ), and green tea catechins have deodorant activities in addition to their antibacterial activities (Kim, Park, Kim, Kim, & Lee, ; Suzuki et al, ; Yasuda & Arakawa, ). Among metal ions, Zn 2+ , along with ions of silver, copper and cadmium, bind directly to VSC, suppressing volatilization (Suzuki et al, ).…”
Section: Inhibition Of Oral Malodormentioning
confidence: 99%
See 1 more Smart Citation
“…Zn 2+ , chlorine dioxide (ClO 2 ), and green tea catechins have deodorant activities in addition to their antibacterial activities (Kim, Park, Kim, Kim, & Lee, ; Suzuki et al, ; Yasuda & Arakawa, ). Among metal ions, Zn 2+ , along with ions of silver, copper and cadmium, bind directly to VSC, suppressing volatilization (Suzuki et al, ).…”
Section: Inhibition Of Oral Malodormentioning
confidence: 99%
“…As described above, Zn 2+ is generally combined with other antibacterial agents in products for controlling oral malodor, and a mouthwash containing Zn 2+ had immediate inhibitory activity against oral malodor (Roldán et al, ; Young et al, ). ClO 2 and the chlorite anion (ClO 2 − ) oxidize VSCs directly into non‐malodorous products, thus consuming the amino acids that act as precursors to VSCs (Kim et al, ). A randomized double‐blind crossover placebo‐controlled clinical trial showed that mouth rinsing with ClO 2 effectively reduced morning malodor for 4 hr in healthy volunteers (Shinada et al, ).…”
Section: Inhibition Of Oral Malodormentioning
confidence: 99%
“…Several chlorine‐containing over‐the‐counter mouthrinses are currently commercially available . Most of these preparations are sold as anti‐halitosis products , but they are also known to have antimicrobial activities .…”
Section: Antimicrobial Mouthrinsesmentioning
confidence: 99%
“…It has been reported that a combination of Zn 2+ and CHX or CPC inhibited VSC formation synergistically [29]. ClO 2 and chlorite anion (ClO 2 -) also oxidize VSCs directly into non-malodorous products, which consumes the amino acids that act as precursors to VSCs [30,31]. A randomized double-blind crossover placebo-controlled clinical trial found that mouth rinsing with ClO 2 effectively reduced morning malodor for 4 h in healthy volunteers [32].…”
Section: Chemical Agentsmentioning
confidence: 99%